Adherence to anti-hypertensive medication in a Malaysian primary care population / Razatul Shima Abdul Razak - Razatul Shima, Abdul Razak (2016)
The objective of this study was to determine the factors affecting non-adherence to anti-hypertensive medication. This study also attempted to develop an instrument to elicit the reasons for non-adherence to anti-hypertensive medication among hypertensive patients in the Malaysian context. This sequential mixed-methods study was utilized among hypertensive patients attending government primary health clinics in Hulu Langat and Klang districts in the state of Selangor, Malaysia between early December 2012 and early April 2014. It was divided into three parts, namely Study Part I, II and III. Study Part I was the quantitative study (pilot study), Study Part II was the qualitative study and Study Part III was divided into two sections, III (a) and III (b). Study Part III (a) comprised items generation and instrument development. Study Part III (b) was the quantitative study (major survey). In Study Part I, 665 participants were involved in the validation of the original version of the Medication Adherence Reasons Scale (MAR-Scale). In Study Part II (qualitative study), the reasons for anti-hypertensive medication non-adherence were explored using in-depth interviews via phenomenological approach involving 25 participants. Study Part III (a) was the process of items generation and the development of self-administered instrument, Medication Adherence Reasons Scale for Malaysian context (myMAR-Scale) was administered to 680 participants. Study Part III (b), (major survey) was conducted among 1200 participants using complex sampling. This quantitative-correlational research methodology was iii conducted to identify factors affecting non-adherence to anti-hypertensive medication. Study Part I verified four factors with 11-items. However, these 11-items could only be applied across gender among the participants. Therefore, Study Part II was conducted to explore in greater detail the reasons for non-adherence to anti-hypertensive medication among Malaysia‘s multi-ethnic population. After examining construct validity and reliability in Study Part III (a), myMAR-Scale resulted with a six factors structure consisting 20 items which was can be used across the major ethnic groups (Malay, Chinese and Indian). In Study Part III (b), four factors were identified to be determinants for high non-adherence among the sampled hypertensive population. These included marital status of divorced/separated/widowed which contributed the most [OR=3.60; 95% CI(1.66, 5.55)], followed by low family support [OR = 3.22; 95% CI(2.51, 3.94)], poor blood pressure control [OR = 2.54; 95% CI(1.78, 3.40)], and participants‘ low concern about their own health [OR = 1.83; 95% CI(1.52, 2.32)]. The revised MAR-Scale in the Malaysian context (myMAR-Scale) demonstrated construct validity and reliability which suitable to be use across gender and ethnicity among the three major ethnic group. There were four factors of non-adherence that determined high non-adherence to antihypertensive medication among hypertensive patients in primary health care settings in Malaysia.